Studi Sosial Ekonomi Pekerja Musim Di PTPN IV Kecamatan Ajung Kabupaten Jember - Muhammad Syahrul Ramadhan Purwanto; Fefi Nurdiana; Nurul Fathiyah Fauzi (Empat Sembilan Publisher, 2025)
Jember Regency is known as one of the main tobacco producing regions in Indonesia. The number of tobacco processing factories has increased labor absorption. Small family income is still the main factor that causes many housewives and even family heads to become seasonal workers: (1) Describe the seasonal worker recruitment system; (2) identify the factors driving workers to become seasonal workers at PTPN I Regional IV; (3) analyze the contribution of seasonal workers' income. This research uses a quantitative descriptive approach with factor identification using a research questionnaire. Sampling used total sampling, which amounted to 40 people. Data collection was done through observation, interviews, literature study, and documentation. Data analysis used intervals from the total answers to the research questionnaire. From the research results it can be concluded that: (1) the recruitment system at PTPN I Regional IV is divided into five stages; (2) the wage indicator is the main driver of someone becoming a seasonal worker; (3) the contribution of seasonal workers' income to family income is moderate with an average percentage of 58.87%..